Breeding status affects fine‐scale habitat selection of southern right whales on their wintering grounds. (11th November 2014) - Rayment, William; Dawson, Steve; Webster, Trudi
Abstract: Aim: To develop and validate a model for fine‐scale distribution of southern right whales ( Eubalaena australis ) on their calving grounds, accounting for breeding status. Location: Port Ross, a harbour at the northern end of the sub‐Antarctic Auckland Islands, approximately 450 km south of mainland New Zealand. Methods: Species–habitat surveys were conducted during annual winter expeditions to the Auckland Islands from 2010 to 2012. Presence locations for groups including calves (calf groups; n  =   462) and not including calves (non‐calf groups; n  =   313) were recorded during small‐boat surveys of Port Ross, and an equal number of pseudo‐absence locations were generated in a GIS analysis. Explanatory variables tested were water depth, seabed slope, distance to coast, distance to shelter from prevailing wind and average wave exposure (estimated from a custom‐built wave model). The occurrence of calf groups and non‐calf groups was separately related to explanatory variables using binomial generalized additive models, with best models chosen via the minimum Akaike information criterion score. Multi‐fold validation was conducted to assess model performance and temporal variation in distribution. Results: The best models for calf groups were consistent, always including wave exposure, distance to shelter, depth and distance to the coastline. In contrast, the best non‐calf group models were more variable and explained only a small proportion of the variation in the data. Validation metrics indicated that the calf group models were useful predictors of distribution in Port Ross during winter, and that the calf group models performed better than the non‐calf models using the same suite of environmental variables. Main conclusions: Breeding female southern right whales seek sheltered, nearshore waters during the early life‐stages of their calves and are more selective of these habitats than non‐calving whales. The results highlight the importance of sheltered habitat for taxa with vulnerable life‐history stages, and the need to account for reproductive status to refine species–habitat models.